2020
DOI: 10.3390/molecules25081920
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Acer okamotoanum Inhibit Adipocyte Differentiation and Promote Lipolysis in the 3T3-L1 Cells

Abstract: Flavonoids, quercitrin, isoquercitrin (IQ), and afzelin, were isolated from ethyl acetate fraction of Acer okamotoanum. We investigated anti-obesity effects and mechanisms of three flavonoids from A. okamotoanum in the differentiated 3T3-L1 cells. The differentiated 3T3-L1 cells increased triglyceride (TG) contents, compared with non-differentiated normal group. However, treatments of three flavonoids from A. okamotoanum decreased TG contents without cytotoxicity. In addition, they showed significant down-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…Acetyl-CoA carboxylase (ACC) is also responsible for the reduction in fatty acid synthesis [16]; in other words, fat accumulation is inhibited by the activation of ACC [17,18]. Adipogenesis can be inhibited by increasing the phosphorylation of both AMPK and ACC [19]. Protein kinase B (Akt) and glycogen synthase kinase-3 beta (GSK3β) are important protein kinases in adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Acetyl-CoA carboxylase (ACC) is also responsible for the reduction in fatty acid synthesis [16]; in other words, fat accumulation is inhibited by the activation of ACC [17,18]. Adipogenesis can be inhibited by increasing the phosphorylation of both AMPK and ACC [19]. Protein kinase B (Akt) and glycogen synthase kinase-3 beta (GSK3β) are important protein kinases in adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it reduced UVB-induced apoptosis and exhibited anti-inflammatory properties by suppressing interleukin-6, tumor necrosis factor-α, and prostaglandin E2 in human keratinocytes [ 24 , 26 ]. Another study using 3T3-L1 adipocytes demonstrated that afzelin treatment moderately decreased adipocyte differentiation partly due to the downregulation of genes associated with adipogenesis, including C/EBPα and FAS [ 27 ]. The in vitro experiment we performed using brown adipocytes demonstrated that afzelin treatment (3 and 10 µM) elevated UCP1-luciferase activity without altering preadipocyte and mature adipocyte cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…First, we kept the mice in a 4 • C cold room for 2 days. Then, the decrease in mice's body temperatures in a cold room was measured every 0, 0.5, 1, 2, 3,17,19,21,23,25,27,42,44,46, and 48 h by inserting a small-diameter temperature probe into the anus (Thermometer DT-610B, CEM). A depth of >2 cm was inserted into mice in a cold room with a 12 h light/dark cycle and free access to food and water.…”
Section: Body Temperature Measurementsmentioning
confidence: 99%
“…Dietary phytochemicals such as flavonoids have been shown to modulate lipid metabolism by increasing basal metabolic rate and thermogenesis [ 18 ]. Kim and colleagues have shown that flavonoids isolated from Acer okamotoanum inhibit adipocyte differentiation and promote lipolysis in the 3T3-L1 adipocytes [ 19 ]. The study also showed significant down-regulation of adipogenic transcription factors, such as γ-cytidine-cytidine-adenosine-adenosine-thymidine/enhancer-binding protein-α, -β, and PPAR-γ.…”
Section: The Relevance Of Flavonoids In Obesity Preventionmentioning
confidence: 99%